Makna Istri Yang Cakap Berdasarkan Amsal 12:4 Sebagai Role Model Perempuan Masa Kini - Reynhard L Ohoitimur (Sekolah Tinggi Teologi Injili Indonesia Yogyakarta, 2023)
Proverbs 12 combines many of Solomon's Proverbs and provides many spiritual lessons. Proverbs 12, says a capable wife is her husband's crown. In today's modern world, the tendency of a woman as a wife to ignore spiritual principles as instructed by Solomon in Proverbs 12:4 is one of the most frequent problems and challenges in Christian families. Christian women must meet several requirements to be considered capable wives. Christian women's desire to be good wives, which is a crown or praise that brings happiness to the family, drives this research. The purpose of writing this article is to determine the true meaning of the phrase,